Igreja Presbiteriana de Cuiabá : tradição, cultura, sociedade e política (1985-2010) - Santos, Sérgio Ribeiro (2015)
The Presbyterian Church of Cuiabá was legally organized in the 20th October 1920, then, in 2015, it is going to be 95 years old. This Protestant, Calvinist and Puritan Church is the oldest non catholic church in Mato Grosso. However, protestant presence in Cuiabá is noticed since the end of 19th Century. This church was founded by Americans missionaries and watched to the great movement of local, national and global transformation order during the last century, including political, social, cultural and economic aspects. As all ancient institution, especially with a conservative bias, it has had to deal with modern times, new ideas and social development that have shaped along its existence, especially at the edge of 20th Century. During the last two decades of the century it faced significant changes in the country, such as democracy transitions, economic opening to international market and the consequences of globalization. Moreover, there were also postmodernity effects, so called by theorists as late modernity. Values and customs, related to ethics, started to be questioned, especially concerned to social behavior, such as family structure, gender issues, sexuality, environment and others. Technology, communication and transport systems were quickly developed and increased dissemination of antagonistic ideas to Puritan and Calvinists values. Under this pressure, Presbyterian Church of Cuiabá has faced a tension caused by the necessity of changes due to this new order and its protestant tradition historically performed. This situation drives it, inevitably, to some moments of contradiction in practical and conceptual terms. Within this scenario, the aim of this research is to understand the way Presbyterian Church of Cuiabá has reorganized itself to this brand new moment of 20th Century final and 21 st Century beginning, moreover to grasp how it has framed its position concerned to tradition and renewal moment. This study will support the thesis that globalization and modernization were the key elements to Presbyterian Church of Cuiabá updating. However it does not mean that it was possible without conflicts of contradictions. This local study will also be useful to understand how historical Protestantism in Brazil has dealt with this phenomenon. This research, inserted in a weberian model, is developed in the field of religions history; nevertheless it keeps an open dialogue with different knowledge areas, with the history of ideas, politic, social and cultural. This study is built especially from documents of Presbyterian Church of Cuiabá, such as Minutes Books, Periodic and oral registers, besides bibliographical and monographic research.